2001
DOI: 10.1002/smj.171
|View full text |Cite
|
Sign up to set email alerts
|

Learning across the life cycle: Experimentation and performance among the hollywood studio heads

Abstract: Guided by notions from the literature on organizational learning, this paper investigates how product line experimentation and organizational performance change across the careers of top managers. Its subjects are the studio heads who ran all the major Hollywood film studios from 1936 to 1965. The study found first, that product line experimentation declines over the course of executive tenures; second, that there is an inverse U-shaped relationship between top executive tenure and an organization's financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
219
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(228 citation statements)
references
References 55 publications
8
219
1
Order By: Relevance
“…In line with previous research listed in Table 1 (Robins 1993;Ravid 1999;Miller and Shamsie 2001), Budget is the movie's final production cost in constant US$ million. It excludes investments in P&A on the basis that distributors, not producers, customarily undertake them.…”
Section: Mediating Variablementioning
confidence: 82%
See 2 more Smart Citations
“…In line with previous research listed in Table 1 (Robins 1993;Ravid 1999;Miller and Shamsie 2001), Budget is the movie's final production cost in constant US$ million. It excludes investments in P&A on the basis that distributors, not producers, customarily undertake them.…”
Section: Mediating Variablementioning
confidence: 82%
“…In line with earlier longitudinal studies of the film industry (Robins 1993;Miller and Shamsie 2001;Nelson et al 2001) and as already indicated, all financial data were converted to constant 1988 US dollars to compensate for inflation. All variables associated with the two lead actors were also aggregated.…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, several studies raise the potential of a non-linear relationship between a CEO's tenure and the firm's performance. Miller and Shamsie (2001) conclude that managers' performance declines after 15 years in office due perhaps to their declining propensity to creativity. This view is shared by Katz (1982), Sonnenfeld (1988), Fernández-Aráoz et al (1988), Hambrick et al (1993); Miller (1991Miller ( , 1994, and Walsh (1995), who suggest that executives who stay on the job too long become 'stale in the saddle'-overly committed to the status and thus less effective.…”
Section: Job Market Variablesmentioning
confidence: 92%
“…We posit that CEOs who have undertaken this type of learning with non-disruptive innovations will be more adept at making the decisions for implementation of disruptive technology. In an evaluation of the performance of production heads in the film industry, Miller and Shamsie [27] observed that studio performance rose before a tenure of 14 -16 years was attained thereby reflecting the benefits of learning and experience. Vintilla and Ghergina [28] used a random sample of 155 companies to measure the relationship between CEO tenure and firm performance.…”
Section: Disruptive Technology and Tenure→net Income→ceo Incentive Paymentioning
confidence: 99%